FAMAJAL (Potret Tradisi Pengakuan Kekerabatan Masyarakat Kampung Lilinta Distrik Misool Barat Kabupaten Raja Ampat Melalui Ritual Keagamaan) - M. Syukri Nawir; Muhamad Yusuf; Talabudin Umkabu; M. Yasin. U.N. Mayalibit; Sulis Maryati (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Famajal is a kinship model that can be found in Papua. This tradition is carried out in religious rituals such as Aqika and Khitan. To strengthen kinship needed donations in the form of money from relatives and guests. In this tradition, there is an acknowledgment of kinship spoken by the money giver and singing a folk song about kinship. This study uses qualitative methods, verbs of social phenomenology with the research area in Lilinta village. the analysis model uses interpretive. The results of the study include 1. Religious rituals in Lilinta such as study in Islamic studies for children, Reciting Surah Yaseen by women, entering new homes accompanied by recitation of the prayer of Manakib, and Reciting Tahlil are a religious unit that is maintained in religious life in the Lilinta village community. 2. Religion can adapt to local culture so cause changes at the surface level. 3. No written source reveals about this tradition so that the tradition has shifted. 4. Not all religious rituals carried out in Lilinta village are combined with Famajal. 7. In Aqikah and Khitanan is not merely ceremonial, in the ritual the child is introduced about the kinship that exists in the family environment with various advice given. 8. Tradition can develop the beliefs, knowledge, and habits (meaning) of the local community which is unique and underlies mutual understanding, develops further interactions and actions in community life and knowledge about kinship.